Athletic activity after total shoulder arthroplasty - Jacobs, C. A. (Medicine and Science in Tennis, 2006)
The purpose of this survey was to categorise current opinions regarding sports activities after TSA. We surveyed 41 members of the American Shoulder and Elbow Surgeons who perform at least five TSAs per year. Surgeons were given a list of 21 activities and asked to categorise each as "allowed", "allowed with prior experience", or "not allowed" following TSA. For each activity, a 75% agreement level between surgeons was set as an indication of consensus. Surgeons categorised the following activities as "allowed": bicycling, bowling, gardening/yard work, golf, horseshoes, jogging, cross country skiing, breaststroke and freestyle swimming, doubles tennis, and weight machines. No consensus was reached regarding specific activities that were "allowed with prior experience" or "not allowed." There were also no consistent clinical criteria used to determine if a patient could return to athletic activity (pain, range of motion, strength, etc.). The majority of surgeons surveyed place lifting restrictions on patients after TSA. In conclusion, this survey provides rough guidelines for postoperative athletic activity following TSA. However, the results underscore the need to develop more concrete, evidence-based activity recommendations. An increase in the number of patients undergoing TSA, combined with an increase in postoperative life expectancy, highlights the void in the literature addressing this topic.